FORMULASI TIWUL INSTAN TINGGI PROTEIN MELALUI PENAMBAHAN LEMBAGA SEREALIA DAN KONSENTRAT PROTEIN KEDELAI (Jurnal Teknologi Industri Pertanian, 2016)
*Penulis untuk korespondensiTiwul is a traditional food (rather chewy, sticky cooked rice-like food made of cassava flour) that is low in protein content and generally has inferior physical characteristics.  The aim of this research was to improve the tiwul quality especially its protein content by formulating instant tiwul using cereal germs flours (corn and wheat) and soy protein concentrate.  The result showed that instant tiwul made of cassava flour-wheat germ flour of 70:30 w/w and soy protein of 3% w/w was higher in protein content than that of cassava flour-corn germ flour in the same proportions, i.e. 11.17 and 5.81%, respectively.  Without soy protein addition, their protein contents were 8.44 and 3.89%, respectively, where as instant tiwul made of 100% cassava flour contained protein of 1.20%. The two substituted instant tiwul had high coefficient of rehydrations, their respective values were 3 - 5 and 2 – 3. Their cooking times were only 8-10 minutes, in comparison to traditional tiwul of 30 minutes. For eliminating of cereal germs flours off-flavors, it was conducted by dipping cereal germs in 2.5% NaCl boiling solution for 3 minutes. In general, their sensory characteristics of cooked instant tiwul were good in texture, flavour, aroma, and colour.Keywords: cassava flour, corn germ flour, instant tiwul, soy protein concentrate, wheat germ flour